Potential for kaolin and bauxite in the near-littoral sediments of the State of Amapá, Eastern Guiana Shield, northern Brazil - Wilson Scarpelli (Journal of the Geological Survey of Brazil)
In Amapá, northern Brazil, there is potential for large and not yet identified economical deposits of kaolin and bauxite in the Cenozoic belt of sediments that cover the margins of the Eastern Guiana Shield next to the Atlantic Ocean and the Amazon River. During geological exploration of these mineral resources, it seems adequate to consider the geological characteristics of the kaolin deposit of Morro do Felipe, at the southwest of Amapá, and the deposits of bauxite replacing Cenozoic kaolin-rich sediments at the coast of Guyana and Suriname. While the Brazilian deposits of bauxite of the Trombetas and Jari rivers occur in topographically stable plateaus, the corresponding plateaus containing bauxite in Guyana and Suriname were lowered to below seawater, and covered by younger sediments. In the southeast of Amapá, sediments similar to some that in Guyana and Suriname are guide to bauxite deposits, as the white sands, appear widespread over a large area. A few but significant exposures of high-grade kaolin suggest high tonnages of the mineral. The presence of these layers of kaolin, the mother-rock of the bauxite of the belt, and the presence of actual paleoduricrust improve the possibility of existence of hidden deposits of bauxite.